Stathmin 1 expression in neuroendocrine and proliferating prostate cancer - Yingli Shi; Yunshin A. Yeh; Siyuan Cheng; Xin Gu; Shu Yang; Lin Li; Nazih P. Khater; Susan Kasper; Xiuping Yu (Discover Oncology)
Abstract Prostate cancer (PCa) is the second leading cause of cancer-related mortality among men in the United States. While PCa initially responds to androgen deprivation therapy, a significant portion progresses to castration-resistant PCa. Approximately 20–25% of these cases acquire aggressive neuroendocrine (NE) features, ultimately leading to neuroendocrine prostate cancer (NEPC). In this study, we investigated the expression of stathmin 1 (STMN1) across PCa subtypes using bioinformatics, western blotting, and immunohistochemical staining analyses in human and murine models. We found that elevated STMN1 expression correlated with high Gleason Scores, increased cell proliferation, and poor clinical outcomes in PCa patients. Notably, STMN1 expression was significantly higher in NEPC compared to prostate adenocarcinoma, suggesting its role in NEPC progression. Findings from TRAMP tumors, a murine NEPC model, further supported these results. In conclusion, STMN1 expression is elevated in advanced PCa, particularly in NEPC, suggesting its involvement in the progression of aggressive forms of PCa. While STMN1 shows potential as a diagnostic and prognostic marker for aggressive PCa, further studies are necessary to establish its clinical utility.